Wokół zarządzania kulturą. Rezultaty badania ankietowego - Wróblewska, Anna; Pawlicka, Kama; Dziurski, Patryk (Załącznik Kulturoznawczy, 2023)
In the spring of 2017 we conducted a survey among researchers in the broadly understood creative sectors, and among managers, often combining experience in this field with academic practice. We asked, among other things, about the cultural management, the specificity of this research area, and the most important environments dealing with this subject. Twenty people responded to our request. The results of this – in fact, self-reflective – research is presented below. Subjective attitude of the respondents to the problems, diversity of positions, and in many points also their convergence form the foundation on which to build research exploration in this area and find, still numerous, white spots.